Devising Ecological and Energy Footprint as Measurement Indicators - Bojan Mihajlovski; Bekim Fetaji; Majlinda Fetaji (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
By analyzing and measuring the values of the personal Ecological and Energy Footprint, as indicators of sustainability, and by using social networks, important information can be obtained about the attitude of the individual toward nature, and the awareness of their impact on the habitat. This analysis would enable us to undertake personal and collective initiatives directed toward a more rational use of the existing resources, as well as raising the quality of life and sustainability. According to statistical data and fact-oriented material which has been collected, it is anticipated that the research will reveal a low awareness among respondents about the impact they have on sustainability with their personal lifestyle. As research methodology used qualitative methodology and to collect the data used questionnaire. Also collected different data from the Ministry of Ecology and later processed them using different Software Tools. Findings, issues and recommendations have been provided, discussed and argumented.
Keywords: A31; 330; Ecological and Energy Footprint; data processing; impact on sustainability; data analytics